Measurement of Resistance to Corn Borer (Ostrina furnacalis, Guinee) in a Composite Variety of Maize - Woerjono Mangoendidjojo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1979)
-